2023
DOI: 10.1111/1751-7915.14203
|View full text |Cite
|
Sign up to set email alerts
|

EndophyticPenicilliumspecies secretes mycophenolic acid that inhibits the growth of phytopathogenic fungi

Abstract: The worldwide demand for reduced and restricted use of pesticides in agriculture due to serious environmental effects, health risks and the development of pathogen resistance calls for the discovery of new bioactive compounds. In the medical field, antibiotic‐resistant microorganisms have become a major threat to man, increasing mortality. Endophytes are endosymbiotic microorganisms that inhabit plant tissues without causing any visible damage to their host. Many endophytes secrete secondary metabolites with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The exogenous spray of a methionine biosynthesis inhibitor, MTX (Scott et al., 2020 ) prevented disease, while methionine treatment enhanced disease severity. Although it remains to be investigated whether methionine can influence plant‐associated microbial populations, that otherwise have a profuse impact on plant health (Azar et al., 2023 ; Das et al., 2021 ; Fitzpatrick et al., 2020 ; Noel et al., 2023 ; Singh, Agrawal, & Bednarek, 2023 ; Singh, Vaishnav, et al., 2023 ). However, we observed that under axenic conditions (during growth in minimal media) methionine treatment facilitated intricate and dense hyphal branching that resemble infection cushions, characteristic structures formed during the necrotrophic phase of R. solani infection in rice (Ghosh et al., 2017 ; Singh et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous spray of a methionine biosynthesis inhibitor, MTX (Scott et al., 2020 ) prevented disease, while methionine treatment enhanced disease severity. Although it remains to be investigated whether methionine can influence plant‐associated microbial populations, that otherwise have a profuse impact on plant health (Azar et al., 2023 ; Das et al., 2021 ; Fitzpatrick et al., 2020 ; Noel et al., 2023 ; Singh, Agrawal, & Bednarek, 2023 ; Singh, Vaishnav, et al., 2023 ). However, we observed that under axenic conditions (during growth in minimal media) methionine treatment facilitated intricate and dense hyphal branching that resemble infection cushions, characteristic structures formed during the necrotrophic phase of R. solani infection in rice (Ghosh et al., 2017 ; Singh et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that endophytes that are recoverable from crops’ wild relatives would be more compatible with the related crops for both inoculation and colonization purposes. For example, the endophytic Penicillium species, isolated from a squill ( Urginea maritima ) leaf, secretes mycophenolic acid, which inhibits the growth of phytopathogenic fungi [ 8 ]. It has been shown that the fungal endophyte Epichloë bromicola, derived from wild barley ( Hordeum brevisubulatum ), has the potential to increase salt tolerance in cultivated barley under salt stress [ 9 ].…”
Section: Introductionmentioning
confidence: 99%